A systematic review on graphene-based nanofluids application in renewable energy systems: Preparation, characterization, and thermophysical properties - Sandhya, Madderla; D., Ramasamy; K., Sudhakar; K., Kadirgama; M., Samykano; W. S. W., Harun; G., Najafi; M., Mofijur; Mohamed, Mazlan (Elsevier, 2021)
Graphene has attracted much attention from various researchers because of its enhanced mechanical, thermal, and physio-chemical properties. Graphene exhibits high thermal conductivity and stability, less erosion and corrosion than other available nanoparticles. Various existing literature signifies a large portion of the research focuses on stability, heat transfer characteristics and thermal conductivity of Graphene nanofluids. This review article represents a detailed analysis of the preparation techniques, characterization methods stability evaluation, and thermal properties enhancements of Graphene nanofluids. Comparative analysis of the effects of nanoparticle size, volume concentration and temperature on thermal conductivity and viscosity of Graphene nanofluids are reviewed based on heat transfer application. Graphene nanoparticles significantly enhances the thermal conductivity, viscosity, and heat transfer capacity of base fluid. It is noticed that the thermal conductivity of Graphene nanofluids increases with an increase in temperature and volume concentration. Applications of Graphene based nano coolant in automotive radiator, electronic cooling, solar cells and fuel cells are presented. This article can be the rapid reference model with investigational and theoretical analysis for highly critical considerations that impact the thermal performance of graphene based nanofluids in different heat transfer trends. This review also outlined the imminent challenges and future scope of research in Graphene.